COMPETITIVENESS AND CHALLENGES OF INDONESIAN CRUDE PALM OIL (CPO) EXPORTS TO THE EUROPEAN MARKET - Syahrudin; I Wayan Suparta (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study analyzes the competitiveness and main challenges faced by Indonesia's Crude Palm Oil (CPO) exports to the European market using a quantitative approach using the Revealed Comparative Advantage (RCA) and Export Competitiveness Index (XCI) methods. Secondary data during the period 2009-2023 was obtained from UN Comrade for four main destination countries, namely the Netherlands, Italy, Germany, and Spain. The results of the RCA analysis show a significant decrease in the comparative advantage of Indonesian CPO in all export destination countries. XCI's analysis indicates high volatility in export competitiveness with value fluctuations between 0.93-1.08. This decline in competitiveness is due to the evolution of increasingly stringent sustainability regulations, increased competition from alternative suppliers, and changing market preferences for sustainable products. This study recommends the development of a strategy for diversifying high-value-added products, the implementation of an integrated sustainable certification system, and the transformation of the CPO industry towards more sustainable practices to maintain competitiveness in the European market.